Seabad Puputan Badung : perspektif Belanda dan Bali - Creese, Helen, 1955-; Putra, Darma; Nordholt, Henk Schulte, 1953- (Denpasar, Bali : Pustaka Larasan, 2006)
History of the Puputan Badung war in 1906 between the Dutch and the Badung Kingdom on Bali; a centennial commemoration volume
In Indonesian, with some texts in Balinese
Keywords: Puputan Badung War, 1906; Bali (Indonesia Province) -- History; Indonesia -- History -- 1748-1942